The responsiveness of Bachelor of Elementary Education curriculum: An illuminative evaluation - Michael Bobias Cahapay (International Journal of Evaluation and Research in Education (IJERE), 2020)
As higher education institutions are pressured to evaluate the responsiveness of their curriculum programs, there is a challenge of first order to define responsiveness. This challenge, however, is compounded by the paucity of a tested evaluation model that addresses it. Thus, this paper aimed to evaluate the responsiveness of the Bachelor of Elementary Education curriculum by attempting the applicability of the model called “illuminative evaluation.” Following the stages and components within the social anthropological framework of the model, multiple methods such as interviews, document reviews, and surveys were employed. The main data analysis technique used was the thematic analysis. The results revealed that illuminative evaluation contextually defined the concept of responsiveness and it effectively uncovered concealed aspects that indicate discrepancies within the curriculum. Thus, given these research outcomes, this work contributes new knowledge to the tradition of evaluation theory and provides practical evidence for the improvement of the curriculum under evaluation. The recommendations are offered at the end of the study.